Gutter treatment for ingrowing toenails. Issue 6183 (21st July 1979) - Wallace, W A; Milne, D D; Andrew, T
Abstract : The gutter treatment for ingrowing toenails consists of introducing a small guard along the side of the toenail and requires only three outpatient attendances. The gutter is left in place for eight to 12 weeks and then removed by the patient. Two studies were carried out to establish the long-term results of the method. In one, a preliminary retrospective study, 13 out of 25 patients who had received the gutter treatment were cured after one year compared with five out of 15 patients in whom the toenail had been avulsed. In a randomised prospective study 20 out of 36 patients (56%) treated by the gutter method were cured after one year compared with 27 out of 32 (84%) in whom the wedge resection procedure had been used. The gutter treatment demands little skill and may be carried out in general practice. It gives an excellent cosmetic result with immediate pain relief and does not compromise further surgery should this be required, thus fulfilling the main requirements for the primary treatment of choice.